ANALISIS YURIDIS TERHADAP PENYALAHGUNAAN APLIKASI MEDIA KOMUNIKASI YANG MENGAKIBATKAN TERJADINYA TINDAK PIDANA PORNOGRAFI - Fajri, Muhammad; Artina, Dessy; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Globalization has been the driver of the birth of the era of information technology development. Therise of deviant behavior among children and adolescents of this country is a concern, among adolescents,for example the phenomenon of pre-marital sexual relations which negates the noble marriage institution,its development has been rapid lately. Criminals see the characteristics of the internet as an opportunity ormeans for them to carry out evil intentions through various actions better known as Cybercrimes. Theenactment of the Electronic Information and Transaction Law or abbreviated as ITE in the cyber world,even though it has been regulated, but it is still difficult to enforce. The object of pornography according tothe Pornography Law) is wider than the object of pornography according to the Criminal Code (Book ofCriminal Law. The Criminal Code (Penal Code) states three, namely writing, drawing, and objects.Pornography containing the contents of the sexual abuse must be formed in a form, for example in the formof images, sketches, illustrations, photos, writings, sounds, sounds, moving images, animations, cartoons,poems, conversations. In this form, there is an obscene content, after the revision of Law Number 11 Year2008 into Law Number 19 Year 2016 concerning Information and Electronic Transactions containingArticle 45 Paragraph 1. And furthermore concerning Law Number 44 Year 2008 Article 4 Paragraph 1Junto (JO) Article 27 concerning Pornography contains Article 4 Paragraph 1. This research is entitled"Juridical Analysis of the Misuse of Communication Media Applications That Result in the occurrence ofPornographic Crimes. Have formulation of the problem What are the legal consequences of the misuse ofcommunication media applications that result in the occurrence of pornography crimes, What is the legalregulation in preventing the misuse of communication media applications that result in pornography crime.In this study using normative research techniques. So the research technique used in data collectionthrough this method requires an active role for the researcher to read the literature in the literature that hasa correlation with the problems being studied. In the study of the literature that the researchers did to obtainsecondary data was done by exploring written sources, including from related literature books that hadrelevance to research problems that were used as complementary and supporting primary data.The author's suggestion, First, there needs to be legislation that regulates clearly and completelyregarding the provision of pornographic restrictions. Second, limiting access to pornography incommunication media so that it does not become a problem that can lead to criminal acts. Third, improvethe national computer network security system according to international standards. Fourth, educating thelaw related to law enforcement so that it can minimize legal consequences in the future.Keywords: Pornography - Cybercrime - ITE - Media Communication